Memory Performance Correlates of Hippocampal Subfield Volume in Mild Cognitive Impairment Subtype - Broadhouse, Kathryn M.; Mowszowski, Loren; Duffy, Shantel; Leung, Isabella; Cross, Nathan; Valenzuela, Michael J.; Naismith, Sharon L. (Frontiers in Behavioral Neuroscience, 2019)
The increased understanding that neuropathology begins decades before symptom onset, has led to the conceptualisation and widespread utilisation of Mild Cognitive Impairment (MCI) as an important transitional state between healthy ageing and dementia. Further subcategorization to MCI subtype has led to more distinct prognoses and it is widely considered that amnestic and non-amnestic MCI (aMCI, naMCI) likely have distinct pathophysiologies. Yet, accurately classification remains contentious. Here we differentiate hippocampal subfield volume between subtypes, diagnosed according to stringent clinical consensus criteria, where aMCI is characterized based on deficits in delayed recall (rather than encoding). We then identify memory performance correlates to subfield volume and associations with long-term cognitive performance and outcome. 3D T1-weighted structural MRI was acquired in 142 participants recruited from the Healthy Brain Ageing Clinic and diagnosed with aMCI (n=38), naMCI (n=84) or subjective memory complaints (SMC; n=20). T1-weighted datasets were processed with the cortical and hippocampal subfield processing streams in FreeSurfer (v6.0). Subfield volumes, and associations with baseline and longitudinal objective memory scores were then examined. Subfield volumes were found to differentiate clinical profiles: subiculum, CA1, CA4 and dentate gyrus volumes were significantly reduced in aMCI compared to both naMCI and SMC. CA1 subfield volume was shown to predict concurrent memory performance in aMCI, while dentate gyrus volume significantly predicted longitudinal verbal learning and memory decline in the entire cohort. Our findings demonstrate that using a more stringent diagnostic approach to characterizing aMCI is well justified, as delayed recall deficits are strongly linked to underlying volumetric subfield reductions in CA1, CA4 and the dentate gyrus, subfields known to be associated with mnemonic processes. Further research is now warranted to replicate these findings in other MCI samples.